Level of Late Initiation of Antenatal Care Visit and Associated Factors Amongst Antenatal Care Attendant Mothers in Gedo General Hospital, West Shoa Zone, Oromia Region, Ethiopia - Debelo, Bikila Tefera; Danusa, Kababa Temesgen (Frontiers in Public Health, 2022)
Background: Antenatal care is a care given for pregnant women and is taken as a key maternal care service in improving and keeping health of both life outcomes for mothers and newborns. Countries with low antenatal care coverage are the countries with very high maternal mortality ratios. Objective: Hence, The aim of this study was to determine the level of late initiation of antenatal care visit and associated factors amongst antenatal care follow up in Antenatal care(ANC) services at Gedo General Hospital, Western Oromia Region, Ethiopia, 2021 Methodology: A health facility based cross-sectional study design was conducted from July 10-30, 2021 using primary data review and face-to-face interviews among clients receiving ANC. A total of 347 mothers was selected by simple random sampling and were interviewed while they come to antenatal care follow-up in Gedo general hospital. Data were entered into Epi-data version 4.6 and then changed to SPSS version 23 for the analysis purpose. Those Variables which are P-values < 0.25 in binary logistic regression were selected as a candidate for multiple logistic regressions to determine independently associated factors. The adjusted odds ratio was employed with 95 % CI to illustrate the strength of association and P-value < 0.05 was used to state a statistical significance. Result: Among 330 women, about 58.5 % of women came for their first ANC visit initiation lately. Being a housewife, having a family size > 4, and having a distance from the health facility > 1 hour were higher odds of late first ANC visit initiation as compared to Vice versa. Besides, Women aged 20-24 years had 0.18 times and 25-29 years had lower odds of late first ANC visit initiation Conclusion: Majority of women began their first antenatal care initiation lately. Therefore, the provision of awareness on the significance of attending the first antenatal care early via health extension workers is recommended